Multi-frequency printed microwave absorber with adjacent absorption peaks by dual-layer technique - Khoomwong, Ekajit; Phongcharoenpanich, Chuwong (My University, 2017)
A multi-frequency printed microwave absorber with very close absorption peaks is designed using a dual-layer technique. The absorption ranges are applicable in the lower WiMAX bands with the adjacent bands (i.e. 2.3/2.7GHz), and also covering almost all U-NII-1/2/3 bands. The absorber consists of two layers with simple rectangular copper patterns, which can improve the modeling and manufacturing accuracy. The design processes are based on numerical simulations. The results show three absorption bands with bandwidths (at 50%) of 140MHz (2.27-2.41GHz), 130MHz (2.68-2.81GHz) and 740MHz (5.025.76GHz). The absorption peaks in each band (i.e. at 2.35, 2.75 and 5.45GHz) are at 98.7%, 85.0% and 99.5%, respectively. The presented absorber exhibits fairly wide-angle characteristics of wave incidence. The advantages of the proposed absorber are thin, simple and low-cost with adjacent absorption peaks, which is suitable for various applications in the lower-band WiMAX and the U-NII frequency ranges, simultaneously.
Keywords: dual-layer; microwave absorber; multi-band; printed circuit board